6 - Knowledge of Sexually Transmitted Diseases among Secondary School Adolescents in Asa Local Government Area of Kwara State Nigeria - Joseph A. Oluyemi; Muhammed A. Yinusa; Raji Abdullateef; Akoh Sunday; Kadiri Kehinde (African Sociological Review, 2015)
The adolescent age is the period of sexual identity when adolescents make sense of their feeling and turn them into actions. This stage requires adequate knowledge of sexual behaviours so that adolescents will not rely on peer group for information. This is because of the far reaching effects it may have on them and the society at large due to misinformation and the consequences of the high risk sexual behaviours they may engage in like sexually transmitted diseases. This study therefore aims at accessing the knowledge and sources of information of STDs among adolescents in the Asa local government area of Kwara State, north central region of Nigeria. The study was carried out in three public secondary schools in Ogbondoroko and Laduba towns, suburbs of the capital city, Ilorin. Information was gathered through questionnaire administration. A total of 240 questionnaires were administered to (SS1), (SS2) and (SS3) students in the study area and in all 210 were retrieved representing 88% return rate. The study made use of tables and simple percentages to present the data retrieved from the field, while the F-test and T-test statistical tools were used to show the relationship between the variables. Findings revealed that adolescents in the study area have a fair knowledge of sexually transmitted diseases. The study also shows a significant relationship between class and knowledge of STDs as test shows a statistical significant relationship P<0.05. While age and sex show no significant relationship with knowledge of STDs as P>0.05.The study suggests that mass enlightenment programmes in schools by government and other relevant agencies in the study area is key to adequate knowledge of STDs in the area.